2007
DOI: 10.1002/pssb.200776205
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes in liquid crystals as versatile functional materials

Abstract: Liquid crystals can be easily aligned in desired directions by treated surfaces or by external fields. The least ordered liquid crystal phase, the nematic, exhibits orientational order that can be easily transferred onto carbon nanotubes dispersed in it. The alignment of the carbon nanotubes can be demonstrated by polarized Raman spectroscopy. Carbon nanotubes not only well integrate in the matrix but also, even at very low concentration, have a detectable effect on the liquid crystal properties that can be ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 9 publications
0
35
0
1
Order By: Relevance
“…The large polarisation dependence of the intensities of both peaks shows that the CNTs and LC are aligned equally. 60 Recently, the polarised Raman technique was employed also to track the electric-field-induced switching of the LC in the vicinity of a SWCNT aggregate that was much too large to allow LC-alignment of the contained nanotubes 21 . 22,23 : some studies report no improvement (often even a deterioration was observed), others report enhancement in some respects while degradation was observed in other parameters (which however were reported to be improved in yet other studies).…”
Section: Cnts In Thermotropic Liquid Crystals 100mentioning
confidence: 99%
“…The large polarisation dependence of the intensities of both peaks shows that the CNTs and LC are aligned equally. 60 Recently, the polarised Raman technique was employed also to track the electric-field-induced switching of the LC in the vicinity of a SWCNT aggregate that was much too large to allow LC-alignment of the contained nanotubes 21 . 22,23 : some studies report no improvement (often even a deterioration was observed), others report enhancement in some respects while degradation was observed in other parameters (which however were reported to be improved in yet other studies).…”
Section: Cnts In Thermotropic Liquid Crystals 100mentioning
confidence: 99%
“…The large polarisation dependence of the intensities of both peaks shows that the CNTs and LC are aligned equally. 60 Recently, the polarised Raman technique was employed also to track the electric-field-induced switching of the LC in the vicinity of a SWCNT aggregate that was much too large to allow LC-alignment of the contained nanotubes 21 . In that case the CNTs influenced the director, rather than the other way 65 around, stabilizing the starting configuration and counteracting the effect of the electric field.…”
Section: Cnts In Thermotropic Liquid Crystals 100mentioning
confidence: 99%
“…a display. Reported effects include reduced effective ion content 16,18,20,21 , increased dielectric anisotropy 16,17,19 , suppressed backflow effects 16,17 , faster 10 electrooptic response due to reduced rotational viscosity 14 and lower switching threshold 16,17,19 . The CNT concentration was in all these works kept extremely low, yet substantial effects were reported.…”
Section: Cnts In Thermotropic Liquid Crystals 100mentioning
confidence: 99%
See 1 more Smart Citation
“…Se sabe que los CNTs presentan distinta intensidad Raman dependiendo de la polarización de la luz que se aplica y si ésta incide paralela o perpendicular al eje largo. De este modo se ha podido detectar en CL nemáticos positivos dopados con CNTs, que éstos siguen al CL cuando se reorienta [140,141]. Mediante el mismo método se ha estudiado la relación de anclaje entre CNTs y CL, y si la composición de las moléculas de CL tiene algún efecto en este proceso [142].…”
Section: Reorientación De Los Cnts Dentro Del CL Y Anclaje Cl -Cntunclassified